Peningkatan Literasi Membaca Bahasa Inggris Anak melalui Picture Books Berbasis Komunitas - Nani Ronsani Thamrin; Erlan Darmawan (Journal of Innovation and Sustainable Empowerment, 2025)
This community service program aimed to improve elementary school children’s English reading literacy through a community-based picture book approach. The program was conducted intensively for one month in Kedungarum Village and involved 25 children aged 9–12 years. The intervention applied visual literacy strategies by integrating text and illustrations through shared reading, interactive storytelling, and post-reading activities. A pre-test and post-test design was used to measure participants’ reading comprehension, focusing on vocabulary mastery, main idea identification, and literal comprehension. The results showed a significant increase in the average score from 41.6 in the pre-test to 72.4 in the post-test, indicating an improvement of 30.8 points. Observational findings also revealed increased student participation, reading confidence, and positive attitudes toward English reading activities. The small-group, community-based model enabled more intensive interaction and individualised feedback, thereby enhancing the intervention's effectiveness. Although differences in participants’ initial abilities posed minor challenges, the overall findings suggest that short-term literacy interventions using picture books can effectively enhance English reading skills among elementary school children. This model can be replicated in similar community settings to strengthen early foreign language literacy development.